Environmental footprints and eco-efficiency of food used in a hospital in Uruguay - Strasburg, Virgílio J.; Dergazarián, Sonia; Scheuer, Junior Miranda; Saadoun, Ali (Sustainability in Debate, 2024)
The foods used to provide meals for communities cause different environmental impacts. This article aimed to identify the environmental impacts of environmental footprints and greenhouse gases (GHG) and calculate eco-efficiency (EE) according to the foods used by a food service at the Hospital de Clínicas (HC) in Montevideo. The foods purchased by the HC in 2021 and the first half of 2022 were evaluated. Of the list of 90 foods, 38 of them were responsible for more than 95% of the amount used. In the evaluation of the variables, eight foods of animal origin represented 33.3% of the total in kg and 52.3% of the economic value, and from 74% to 89.7% in terms of the footprints evaluated. The amount used and the place of origin of some foods directly influenced the GHG results found.